Noncovalent Liquid Phase Functionalization of 2H-WS2with PDI: An Energy Conversion Platform with Long-Lived Charge Separation - Scharl, Tobias; Binder, Gerhard; Chen, Xin; Yokosawa, Tadahiro; Cadranel, Alejandro; Knirsch, Kathrin; Spiecker, Erdmann; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Transition metal dichalcogenides are attractive 2D materials in the context of solar energy conversion. Previous investigations have focused predominantly on the properties of these systems. The realization of noncovalent hybrids with, for example, complementary electroactive materials remains underexplored to this date for exfoliated WS2. In this contribution, we explore WS2 by means of exfoliation and integration together with visible light-absorbing and electron-accepting perylene diimides into versatile electron-donor acceptor hybrids. Important is the distinct electron-donating feature of WS2. Detailed spectroscopic investigations of WS2-PDI confirm the electron donor/acceptor nature of the hybrid and indicate that green light photoexcitation leads to the formation of long-lived WS2+-PDIcharge-separated states.
CRIS-Team Scopus Importer:2022-04-14